2001
DOI: 10.1212/wnl.57.6.1032
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal nicotine in PD

Abstract: With the dosage and the period of treatment chosen, transdermal nicotine patches are not effective as an add-on treatment for symptoms of PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(88 citation statements)
references
References 17 publications
2
85
0
1
Order By: Relevance
“…To date, administration of the nicotine patch and/or gum has yielded conflicting results, with some studies reporting small improvements in motor and cognitive deficits and others no effect or a decline (Ishikawa and Miyatake, 1993;Fagerstrom et al, 1994;Ebersbach et al, 1999;Kelton et al, 2000;Vieregge et al, 2001;Lemay et al, 2004). Drawbacks of these studies include the limited number of subjects and very short duration (2-4 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…To date, administration of the nicotine patch and/or gum has yielded conflicting results, with some studies reporting small improvements in motor and cognitive deficits and others no effect or a decline (Ishikawa and Miyatake, 1993;Fagerstrom et al, 1994;Ebersbach et al, 1999;Kelton et al, 2000;Vieregge et al, 2001;Lemay et al, 2004). Drawbacks of these studies include the limited number of subjects and very short duration (2-4 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the apparent protective effect of smoking, the therapeutic effect of nicotine has been tested in a few clinical trials, but no improvement of motor symptoms with transdermal nicotine treatment has been documented [668,669]. Moreover, on the basis of the apparent protective effect of coffee in PD, adenosine receptor (A 2A ) antagonists have also been tested and there is evidence that they improve parkinsonian symptoms in animal models [670] and clinical trials [671][672][673][674].…”
Section: Comments and Perspectivesmentioning
confidence: 99%
“…Kelton and co-workers [52] observed improvements in areas of cognitive performance and motor measures after treatment with intravenous nicotine and the nicotine patch, with effects sustained for up to 1 month after the drug. However, Vieregge et al observed no improvements in patients administered the patch for 3 weeks [53], although the lack of efficacy may have related to the fact that Parkinsonism was only assessed 3 weeks after patch cessation. On the other hand, Lemay et al [54] also obtained no improvement in motor or cognitive deficits with immediate testing of Parkinson's disease symptoms after 3 to 4 weeks of treatment.…”
Section: Nicotine and Nicotinic Agonists For The Symptomatic Treatmenmentioning
confidence: 99%